2021
DOI: 10.1002/jev2.12069
|View full text |Cite
|
Sign up to set email alerts
|

Identification of anti‐inflammatory vesicle‐like nanoparticles in honey

Abstract: Honey has been used as a nutrient, an ointment, and a medicine worldwide for many centuries. Modern research has demonstrated that honey has many medicinal properties, reflected in its anti‐microbial, anti‐oxidant, and anti‐inflammatory bioactivities. Honey is composed of sugars, water and a myriad of minor components, including minerals, vitamins, proteins and polyphenols. Here, we report a new bioactive component‒vesicle‐like nanoparticles‒in honey (H‐VLNs). These H‐VLNs are membrane‐bound nano‐scale particl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 65 publications
0
68
0
1
Order By: Relevance
“…Honey is another bee product that has antimicrobial, anti-inflammatory, and antioxidant properties. Chen et al reported a new bioactive component-vesicle-like nanoparticles (H-VLNs) in honey that shows anti-inflammatory activities [261]. H-VLNs can disrupt a crucial inflammatory signaling platform in the innate immune system by restraining the formation and activation of the nucleotide-binding domain and pyrin domain-containing 3 (NLRP3) inflammasome.…”
Section: Bee Product-derived Nanoparticles As Potential Therapeutic Agentsmentioning
confidence: 99%
“…Honey is another bee product that has antimicrobial, anti-inflammatory, and antioxidant properties. Chen et al reported a new bioactive component-vesicle-like nanoparticles (H-VLNs) in honey that shows anti-inflammatory activities [261]. H-VLNs can disrupt a crucial inflammatory signaling platform in the innate immune system by restraining the formation and activation of the nucleotide-binding domain and pyrin domain-containing 3 (NLRP3) inflammasome.…”
Section: Bee Product-derived Nanoparticles As Potential Therapeutic Agentsmentioning
confidence: 99%
“…Honey contains different bioactive molecules including p-coumaric acid, eugenol, ferulic acid, caffeic acid, pinobanksin, pinocembrin, chrysin, quercetin, apigenin, galangin, isorhamnetin, gallic acid, kaempferol, syringic acid, luteolin and naringin; nevertheless, their concentrations vary depending on the type of honey (Ciulu et al, 2016;da Silva et al, 2016;Shen et al, 2019). In addition, a novel study has recently identified vesicle-like nanoparticles (VLNs) as a new bioactive agent in honey (Chen et al, 2021).…”
Section: Anti-inflammatory and Antioxidant Effects Of Honeymentioning
confidence: 99%
“…Another recent study has shown the biological role of honey-derived VLNs which exert a potent anti-inflammatory activity by suppressing NLRP3 inflammasome activation and NF-κB signaling. Furthermore, small-sized RNAs were identified as the molecules that remarkably ameliorated NLRP3 inflammasome activity, specifically, miR-4057 protected mice from acute inflammatory conditions in the liver (Chen et al, 2021). On other hand, different studies have explored the effects of honey intake on malondialdehyde and ROS levels in athletes and murine models, where individuals were subjected to high-impact exercise regimens.…”
Section: Anti-inflammatory and Antioxidant Effects Of Honeymentioning
confidence: 99%
“…Namely, ELV from honey and royal jelly significantly increased migration of mesenchymal stem cells what is thought to be one of the crucial steps in mammalian wound healing models to assist in immunomodulation, recruitment of fibroblasts and regeneration [ 105 ]. Recently, Chen et al (2021) identified vesicle-like nanoparticles (VLN) in honey as new bioactive components [ 106 ]. The authors confirmed the presence of plant-originated plasma transmembrane proteins and plasma membrane-associated cytosolic proteins in VLN but failed to detect tetraspanins, a well-established EV marker.…”
Section: Extracellular Vesicles As New Nutraceuticals From Bee Productsmentioning
confidence: 99%